Formulasi Campuran Bahan Pengemulsi untuk Bolu Sponge - Hanifah N. Lioe; Aida Fadhilah; Istiqamah Istiqamah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
To make a sponge cake, a mix of emulsifiers provides an improved aeration. The aim of this research was to formulate the mix of distilled monoglycerides (DMG) and polyglycerol esters (PGE), which had yellowish color, in a gel form for its application in sponge cake. The formula of the gel consists of primary and secondary food additives: 15.3% DMG, 6.5% PGE, 25.8% other emulsifiers and carrier including colorings (ponceau and tartrazine), 26.1% sorbitol, and 26.3% water. DMG and PGE had different colors from their expected standard color, white. The formula of DMG (15.3%) and PGE (6.5%) mix, comprising 21.8% of the formula above, was re-formulated by 100:0, 75:25, 50:50, 25:75, and 0:100 ratios of DMG to PGE. The physical characteristics of the formula consisting of color characteristic by chromameter, sensory score by R-Index method and gel spreadability were compared to the formula using standard materials of DMG and PGE. The formula was then applied for sponge cake. The specific gravity of sponge cake batter, height of sponge cake after baking, as well as sensory characteristics of crumb structure and crumb color of sponge cake were analyzed. The results of physical characterization of formula revealed that the use of 100% of PGE and the use of DMG up to 50% did not significantly differ from the standard formula. The combination of DMG and PGE formula did not affect batter specific gravity, cake height and crumb structure, but affected color of the crumb.